Paper alert. Immunology. - Elliott, T; Bonneville, M; Kruisbeek, A; Walker, P; Glaichenhaus, N; Rowland-Jones, S; Casanova, J; Liu, Y; Wood, K; Bushell, A; Green, A (2001)
A selection of interesting papers that were published in the two months before our press date in major journals most likely to report significant results in immunology.